Screening low-methanol and high-aroma produced yeasts for cider fermentation by transcriptive characterization - Liu, Liang; Zhao, Peng Tao; Hu, Ching Yuan; Tian, Dan; Deng, Hong; Meng, Yong Hong (Frontiers in Microbiology, 2022)
The commercial active dry yeast strains used for cider production in China are far behind the requirements of the cider industry development in recent decades. In this study, eight yeasts, including Saccharomyces cerevisiae, Schizosaccharomyces pombe, Pichia bruneiensis, and Pichia kudriavzevii, were screened and assessed by growth performance, methanol production, aroma analysis, and their transcriptive characterization. Saccharomyces cerevisiae strains WFC-SC-071 and WFC-SC-072 were identified as promising alternatives for cider production. Strains WFC-SC-071 and WFC-SC-072 showed an excellent growth capacity characterized by 91.6% and 88.8% sugar utilization, respectively. Methanol production by both strains was below 200 mg/L. Key aroma compounds imparting cider appreciably characteristic aroma increased in cider fermented by strains WFC-SC-071 and WFC-SC-072. RT-qPCR analysis suggested that most genes associated with growth capacity, carbohydrate uptake, and aroma production were upregulated in WFC-SC-071 and WFC-SC-072. Overall, two Saccharomyces cerevisiae strains are the optimal starters for cider production to enable the diversification of cider, satisfy the differences in consumer demand, and promote cider industry development.